Evaluation Methods for Assessing Users' Psychological Experiences of Web-based Psychosocial Interventions: A Systematic Review - Feather, JS; Howson, M; Ritchie, L; Carter, PD; Parry, DT; Koziol-McLain, Jane (JMIR Publications, 2016)
The use of Web-based interventions to deliver mental health and behavior change programs is increasingly popular. They are cost-effective, accessible, and generally effective. Often these interventions concern psychologically sensitive and challenging issues, such as depression or anxiety. The process by which a person receives and experiences therapy is important to understanding therapeutic process and outcomes. While the experience of the patient or client in traditional face-to-face therapy has been evaluated in a number of ways, there appeared to be a gap in the evaluation of patient experiences of therapeutic interventions delivered online. Evaluation of Web-based artifacts has focused either on evaluation of experience from a computer Web-design perspective through usability testing or on evaluation of treatment effectiveness. Neither of these methods focuses on the psychological experience of the person while engaged in the therapeutic process.
Keywords: Web-based; Computer systems; eHealth; eHealth evaluation; Medical informatics applications; Psychology, clinical; Usability; Usability testing; Web browser